Organizational health and quality of life: survey among ambulance nurses in prehospital emergency care / Salute organizzativa e qualità della vita: indagine tra gli infermieri delle ambulanze territoriali - Sili, A.; Fida, R.; Vellone, et al., E. (La Medicina del Lavoro, 2011)
Summary Background: The workplace plays a central role in causing stress and different kinds of syndromes and diseases. More generally, organizational procedures and practices could have an impact on nurses’ quality of life. Although several studies have investigated this link, none of them considered nurses working in prehospital emergency care. Objectives: To investigate the role of organizational health factors that affect the quality of life and psychosomatic complaints of ambulance nurses. Method: Our sample included 411 ambulance nurses. Workers were administered two questionnaires to assess organizational health and quality of life. Descriptive and correlational analyses were used to test our assumptions. Conclusion: Several organizational health dimensions provided an explanation for the complaints reported by nurses working in prehospital emergency care in terms of quality of life and psychosomatic disorders. The results allowed identification of possible interventions focusing on specific duties and organizational aspects that would improve the quality of nurses’ health. Riassunto Introduzione: Il contesto lavorativo gioca un ruolo centrale nel determinare alti livelli di stress e nello sviluppare distubi di diversa natura. Più in generale i processi e le pratiche organizzative possono avere un impatto sulla qualità della vita degli inferimieri. Sebbene diversi studi abbiano indagato queste relazioni causali, nessuno di questi ha approfondito tali tematiche tra gli infermieri che lavorano nelle ambulanze. Obiettivi Esaminare quanto i fattori della salute organizzativa incidano sulla qualità della vita e sui disturbi psicosomatici degli infermieri che prestano servizio nelle ambulanze. Metodi: Il nostro campione è composto da 411 infermieri che lavorano nelle ambulanze dell’emergenza territoriale. Ai lavoratori sono stati somministrati due scale: una per misurare la salute organizzativa, l’altra per valutare la loro qualità di vita. Per esaminare le ipotesi sono state effettuate un’analisi descrittiva e una correlazionale. Conclusioni: Diverse dimensioni della salute organizzativa spiegano la qualità della vita e i disturbi psicosomatici degli infermieri che lavorano nell’emergenza. I risultati consentono di identificare possibili interventi su specifici aspetti dell’organizzazione che possono contribuire a migliorare la qualità della vita degli infermieri.